PENGAWASAN KEPALA INSPEKTORAT TERHADAP KINERJA APARATUR SIPIL NEGARA DIJABATAN STRUKTURAL INSPEKTORAT PROVINSI KALIMANTAN TENGAH - INDAH SUBEKTI (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2017)
This study aims to determine the supervision of the Inspectorate's head on the performance of the Civil State Apparatus in the structural position of the Inspectorate of Central Kalimantan Province. Indicators used in measuring supervision Inspectorate head in this research are: Monitoring, Examination, Guidance and Direction, Discipline Action and Corrective Action.This research was conducted by using qualitative methodology, by conducting interviews to the Chief Inspectorate. The data obtained is then processed by reduction steps, data presentation and conclusion, the number of informants interviewed are 5 persons, 1 (one) Head of Inspectorate, 2 (two) Head of Section in Structural Position and 2 (two) State Civil Apparatus in Structural Position.Based on the results of research on the supervision of Inspectorate's head on the performance of State Civil Apparatus has been running but still not done with the maximum this is caused by every activity or work program is sometimes not submitted by each head of section and in accordance with supervision provisions seen from monitoring, examination, guidance and briefing, Disciplinary action and corrective action. Because basically State Civil Apparatus is the most important Human Resources for orgnanisasi in achieving its goals. In order for the objectives to be achieved then required supervision by the direct leadership.Factors that support and inhibit the supervision of the head of Inpektorat on the performance of the State Civil Apparatus include the supporting factors that is in terms of recording procedures and reporting of work program activities as well as in terms of absence or attendance, inhibiting factors include pakewuh culture, limited time and in terms of aspects of Civil State Apparatus That is character difference.